Level Boosting DC-DC Converter for Solar Energy Conversion System - Komarasamy, Ramesh; Kailasam, Mahalakshmi; P, Sreenath; V, Srimaheswaran; P, Ponmurugan (International Journal of Engineering and Technology, 2018)
The conversion of light energy into electrical energy has extensively increasing because it offers less pollution and its wide availability. Maintaining the constant DC output power from the panel is the key issue in solar PV system. Solar irradiation and temperature of the solar cells are the two factors effects the output of the PV modules, in the proposed converter. To get better conversion gain ratio the Switched Inductor/Capacitor Branch is replacing the existing inductor in the conventional boost converter. The conduction loss can be lessened by adopting the switch with low resistance. In addition, the reverse-recovery issue of the diodes is eliminated, and thus, the efï¬ciency can be further improved. In this paper, Perturb and Observe (P&O) algorithm is used along with proposed boost converter to track the MPPT from the solar cell and to improve the DC output by providing suitable duty cycle. The number of components used in converter has been reduced and converter efficiency is improved. The proposed work is verified through MATLAB/SIMULINK.Â Â